A review on architectural and urban design approaches to reducing the urban heat island effect - Yu, Chiu Hung; Ling, Gabriel Hoh Teck; Huang, Chih-Hong; Leng, Pau Chung; Nur Amiera Md Suhud,; Ho, Wai Shin (Penerbit Universiti Kebangsaan Malaysia, 2022)
With the ongoing rapid urbanisation, humans enjoy the comfort of living with the use of advanced technology and infrastructure, without consideration towards the pollution produced daily, such as waste, heat, and exhaust gas emissions. Human-induced climate change has resulted in extreme weather and climate events, causing a consequential increase in the urban heat island effect. A large amount of radiant heat is focused in the city area, threatening the threshold of comfort in urban living, affecting our future generations to come. Therefore, this paper discusses how this phenomenon could be mitigated through a few design approaches. The existence of green roofs helps reduce the direct absorption of heat in buildings while water bodies help lower the surrounding temperature of a place. Additionally, using high reflectivity and spectral emissivity materials in buildings can also lower heat absorption into a building. Also, the design of urban wind corridors increases airflow into an area, hence cooling the surrounding temperature. When these steps are strategically incorporated into a design, the amount of heat could be significantly reduced, hence extenuating the urban heat island effect. However, more in-depth research is needed to ensure that it could successfully palliate the urban heat island effect in a city. It is hoped that this study could be a comprehensive guide to designers and engineers, or any individuals in the field of architecture and urban design in tackling the problem, hence achieving their target in eliminating the urban heat island effect in future works.